Analisis Laporan Arus Kas dalam Menilai Kinerja Keuangan di Badan Penyelenggara Jaminan Sosial Kesehatan - Reni Laelasari; Faisal Rakhman (Jurnal Dimamu, 2022)
The background of this research is the cash flow at BPJS Kesehatan has decreased every year due to the company’s expenses exceeding the income earned. This study aims to determine the financial performance of BPJS Kesehatan for the 2017-2021 period by using cash flow liquidity and cash flow flexibility ratios. The object of this research is the BPJS Kesehatan financial report for the 2017-2021 period which includes balance sheet, income statement and cash flow statement. The type of this research used is quantitative research with a descriptive approach. The type of data is secondary data. The results of this study are the cash flow liquidity ratio based on the operating cash flow ratio and the capital expenditure ratio in 2017 is good because it is above standard 1, but in 2018-2021 it shows a poor ratio because it is below standard 1, then the total debt ratio from 2017-2021 shows a poor ratio because it is still below standard 1. Based on the cash flow flexibility ratio, namely the cash flow adequacy ratio and the net free cash flow ratio of 2017-2021 shows a ratio below standard 1 which means BPJS Kesehatan financial performance is not good.